From Cognitive Skill To Intellectual Disposition: An Affective Internalization Model Of Critical Thinking In Arabic Language Learning Among Madrasah Aliyah Students - Dibi Afriansyah; Wildana Wargadinata; Syuhadak Syuhadak; Muhammad 'Ainul Haq (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study addresses a critical gap in language education, where critical thinking is often treated as a situational cognitive skill rather than a sustained intellectual disposition. It examines how affective internalization shapes the development of critical thinking in Arabic language learning. A qualitative case study was conducted over eight weeks, involving sixteen classroom observations, semi-structured interviews (2 teachers and 12 students), and document analysis, with data analyzed thematically based on Krathwohl’s affective domain. The findings show that critical thinking develops through five stages: receiving, responding, valuing, organization, and characterization, mediated by affective engagement in classroom practices. Most students remained at transitional stages (receiving–responding: 55%), while fewer reached dispositional levels (organization–characterization: 25%). Dialogic interaction, text interpretation, and reflective reasoning facilitate the shift from externally guided responses to internally regulated thinking. This study demonstrates that critical thinking develops through affective internalization rather than cognitive training alone and proposes an integrative model linking affective and cognitive processes. However, this study is limited to a single institutional context, which may affect the generalizability of the findings.